2008
DOI: 10.1128/mcb.00114-08
|View full text |Cite
|
Sign up to set email alerts
|

Freud-1/Aki1, a Novel PDK1-Interacting Protein, Functions as a Scaffold To Activate the PDK1/Akt Pathway in Epidermal Growth Factor Signaling

Abstract: The phosphoinositide 3-kinase (PI3K)/3-phosphoinositide-dependent protein kinase 1 (PDK1)/Akt pathway regulates various cellular functions, especially cell survival and cell cycle progression. In contrast to other survival pathways, there have been few reports of scaffold proteins that regulate signaling cascade specificity in this pathway. Here we identify a 5 repressor element under dual-repression binding protein 1 (Freud-1)/Akt kinase-interacting protein 1 (Aki1) as a novel scaffold for the PDK1/Akt pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Our work has indicated that CC2D1A binds PIP3, thus it is possible that the increased rate of Akt activation may be dependent on the lipid binding properties of CC2D1A. Consistent with this, it was revealed that CC2D1A function required the presence of the fourth DM14 domain, as ablating this domain abrogated the interaction between CC2D1A and Akt/PDK1 (Nakamura, et al, 2008). This requirement for the fourth DM14 domain is significant given that a point mutant in this domain abrogated lipid binding (Millar, et al, 2011) and it is clinically relevant as the domain is absent in the CC2D1A mutation present in NSMR.…”
Section: Cc2d1a and Akt Functionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our work has indicated that CC2D1A binds PIP3, thus it is possible that the increased rate of Akt activation may be dependent on the lipid binding properties of CC2D1A. Consistent with this, it was revealed that CC2D1A function required the presence of the fourth DM14 domain, as ablating this domain abrogated the interaction between CC2D1A and Akt/PDK1 (Nakamura, et al, 2008). This requirement for the fourth DM14 domain is significant given that a point mutant in this domain abrogated lipid binding (Millar, et al, 2011) and it is clinically relevant as the domain is absent in the CC2D1A mutation present in NSMR.…”
Section: Cc2d1a and Akt Functionsupporting
confidence: 79%
“…Given that Akt signalling is a developmentally significant pathway, it is of interest that it has been shown to be regulated by CC2D1A (Nakamura, et al, 2008). As mentioned, CC2D1A is localized to both the cytoplasm and the nucleus , thus it is reasonable to presume that its location within the cell determines its primary function, with nuclear localization being pertinent to transcriptional regulation and cytoplasmic localization relating to Akt-mediated cell survival.…”
Section: Cc2d1a and Akt Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation of Grb14 in the PDK1-binding motif revealed a significant reduction in insulin-dependent Akt activation, which suggested the role of Grb14 as an adapter molecule for the modulation of the membrane association of PDK1 in response to insulin (King and Newton, 2004). Freud1/Aki1 interacts with both the catalytic and PH domains of PDK1 and Akt and activates Akt signaling in EGF receptor-mediated signaling (Nakamura et al, 2008;Yamada et al, 2013). Given Grb14 and Freud/Aki1 are scaffolding components that facilitate the localization of PDK1 to the plasma membrane to activate Akt, the context-dependent optimal activation mechanism of PDK1 and Akt was apparently required.…”
Section: Discussionmentioning
confidence: 98%
“…Second, some functions of PDK1 may be independent of interaction with AGC kinases. For example, several non-AGC kinase proteins have been identified in mammals that are required for PDK1 function (Nakamura et al, 2008;Sephton et al, 2009). Finally, interaction of PDK1 with some substrates is independent of PIF binding (Collins et al, 2003).…”
Section: The Pppdk1 Knockout Is Developmentally Compromisedmentioning
confidence: 99%